2000
DOI: 10.1152/jn.2000.83.5.3042
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Modulation of Substantia Nigra Pars Reticulata Neurons

Abstract: Neurons in the substantia nigra pars reticulata (SNr) are known to encode saccadic eye movements within some, but not all, behavioral contexts. However, the precise contextual factors that effect the modulations of nigral activity are still uncertain. To further examine the effect of behavioral context on the SNr, we recorded the activity of 72 neurons while monkeys made saccades during a delayed saccade task and during periods of free viewing. We quantified and compared the movement fields of each neuron for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
(40 reference statements)
5
35
0
1
Order By: Relevance
“…Under these "quiet, resting conditions," environmental factors as well as physiological cycles can affect SNr cells and, consequently, change their responsiveness to GLU. Several studies revealed that the activity of SNr neurons is modulated by environmental context (Handel and Glimcher, 2000;Gulley et al, 2002) and by continuous oscillations of the wake-sleep cycle naturally occurring during quiet, resting conditions during day- time recording (Miller et al, 1983). Because the activity of serotonin-containing neurons and serotonin release varies depending on the sleep-wakefulness cycle (for review, see Portas et al, 2000) and because this neurotransmitter has direct postsynaptic effects on SNr neurons via 5-HT 2c receptors and is involved in presynaptic regulation of GABA release via 5-HT 1b receptors (Rick et al, 1995;Stanford and Lacey, 1996), fluctuations in serotonin activity may be a factor determining the variability of basal activity and GLU responsiveness of SNr neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Under these "quiet, resting conditions," environmental factors as well as physiological cycles can affect SNr cells and, consequently, change their responsiveness to GLU. Several studies revealed that the activity of SNr neurons is modulated by environmental context (Handel and Glimcher, 2000;Gulley et al, 2002) and by continuous oscillations of the wake-sleep cycle naturally occurring during quiet, resting conditions during day- time recording (Miller et al, 1983). Because the activity of serotonin-containing neurons and serotonin release varies depending on the sleep-wakefulness cycle (for review, see Portas et al, 2000) and because this neurotransmitter has direct postsynaptic effects on SNr neurons via 5-HT 2c receptors and is involved in presynaptic regulation of GABA release via 5-HT 1b receptors (Rick et al, 1995;Stanford and Lacey, 1996), fluctuations in serotonin activity may be a factor determining the variability of basal activity and GLU responsiveness of SNr neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although the connections within the cortico-striato-thalamic "loops" are well defined chemically (excitatory or inhibitory), none of them have individually been assigned a specific role in motor response inhibition. For instance, despite the focus of earlier unit recording studies on saccade-related tonic-pause neurons, more recent work have documented saccade-related "burst" neuronal responses, in the pars reticulata of the substantia nigra, an output nucleus of the basal ganglia (Bayer et al, 2004;Handel and Glimcher, 1999;Handel and Glimcher, 2000;Hikosaka and Wurtz, 1983a;Hikosaka and Wurtz, 1983b;Sato and Hikosata, 2002).…”
Section: Role Of Subthalamic Nucleus During Visual Motor Processingmentioning
confidence: 99%
“…In rats working for sucrose reinforcement, for example, a dose of amphetamine that activated behavior without impairing performance had no effect on the pattern of the SNr response, but significantly altered the relative magnitude of the neuronal change in relation to specific components of the operant task (Gulley et al, 2002a). Context also appears critical for SNr involvement in normal, non-drug-related movement (Handel and Glimcher, 2000). Further research is needed to assess how striatal information is integrated into ongoing SNr activity.…”
Section: Amphetamine Effects In Snrmentioning
confidence: 99%